Cefepime-induced neurotoxicity in a patient with renal dysfunction: a case report - Daniela V. SILVA; Cleni VERONEZE; Priscila L. GUIMARÃES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Cefepime is an antimicrobial widely used in the hospital environment. During the development phases, the drug proved to be safe and, therefore, was approved and marketed. After the commercialization of cefepime, case reports involving a serious adverse reaction were emerging. Cefepime-Induced Neurotoxicity (CIN) is a reaction that occurs most often in patients with renal dysfunction, damage to the blood-brain barrier or advanced age. Dose adjustment should be made according to creatinine clearance in order to prevent adverse reaction. Among the symptoms are drowsiness, tremors, myoclonus, agitation, lowered level of consciousness, convulsions and coma. The electroencephalogram can be used to aid in the diagnosis, but it is not specific for this condition. In this article, we present a case report of a 52-year-old woman with acute renal failure who presented CIN after using cefepime, despite dose adjustments according to renal function. The patient presented the symptoms even after discontinuing the medication and hemodialysis did not reverse the condition. The patient's physiological characteristics may have contributed to the outcome of the case. The description of CIN cases in the literature is important for a better understanding of the pathophysiology that involves the adverse reaction and prevention of new cases.